INTELLECTUAL DEVELOPMENT OF FUTURE PRIMARY TEACHERS BASED ON AN INDIVIDUAL APPROACH – AS A PEDAGOGICAL PROBLEMindividual yondashuv, intellektual rivojlantirish, boshlang‘ich sinf o‘qituvchilari, pedagogik muammo, interaktiv metodlar, kreativ pedagogika (Universal International Scientific Journal, 2026)
This article analyzes the importance and pedagogical problems of an individual approach in the process of intellectual development of future primary school teachers. Effective methods of intellectual development of students, pedagogical problems, innovative technologies and methodological solutions are considered. It is emphasized that an individual approach serves to increase the creative and cognitive potential of future teachers, as well as to improve the quality of the pedagogical process.
Keywords: individual approach, intellectual development, primary school teachers, pedagogical problem, interactive methods, creative pedagogy